Global Sustainable Development Goals through the lenses of Social Work Students in Australia and Bosnia and Herzegovina – Comparative Research - Janjetović, Vesna Šućur-; Lepir, Ljubo; Šćepović, Dragana (European Journal of Social Science Education and Research, 2023)
The Research Project was directed towards the research on opinions of future social workers (current students) in two different socio-economically developed societies, in Bosnia and Herzegovina and Australia. The focus of this research were the opinions and attitudes amongst future social workers about strategic directions of societies’ global developments defined by the Global Sustainable Development Agenda 2015-2030 (SDGs). The method for data collection used in this research was a specifically designed online survey. The main findings indicate that most of the social work students in both countries are not familiar with the SDGs, as well as that students of social work see the role of social workers in permanent critiquing and challenging the constrains of capitalism and social systems that create unjust societies. Such systems entrench inequality and poverty in society, regardless of their socio-economic development. The study identifies difference in opinion concerning the values important for family, community and profession of social work which is in correlation with the difference in socio-economic development of the two countries. The findings of this study also identify similarities in social work students’ opinions and attitudes regarding the future development and social work issues, both at the global and local level of communities. Finally, this article also includes some ideas and discussions for future research directions on similar topics.
Keywords: social work students, global sustainable development goals, social work education